Rotator cuff disorders: A survey of current physiotherapy practice in Turkey - ÖZGÜL, BAHAR; POLAT, MİNE GÜLDEN (My University, 2023)
Purpose: One of the most important factors guiding the physiotherapy program for rotator cuff disorders (RCD) is the clinical preferences of the physiotherapist in light of the evidence. However, the management parameters are remarkably variable between physiotherapists. It was aimed to describe the current physiotherapy practice of Turkish physiotherapists for the management of RCD and to explore its parallelism with the research evidence, and with the clinical perspective in European Countries. Methods: A cross-sectional online survey based on a clinical scenario that describes a typical patient with symptoms of RCD was conducted during July/August 2020. Descriptive responses of 104 physiotherapists were reported and analyzed by grouping physiotherapists with special interest (SI) who have further clinical experience or specialized training on RCD and no special interest (NSI). Results: The most preferred approaches were mobilization (82), scapular stabilization exercises (82), advice/education (71), and taping (62) considering all the participants. The preference rate of cold therapy (χ2=4.303, p=0.038) and isometric exercises (χ2=4.248, p=0.039) were significantly higher for physiotherapists with SI rather than NSI group. Conclusions: The most preferred management strategies of mobilization, exercise, and advice/education have been aligned with the preferences of physiotherapists from European countries and the current research evidence. However, passive modalities were also highly preferred. The management strategies differ between the physiotherapists who have SI and NSI. The high degree of practice variability and passive treatment preference of physiotherapists for the patients with RCD might be due to a lack of following the current literature evidence regularly.